CORRELATION OF NUTRITIONAL STATUS WITH THE INCIDENCE OF ACUTE DIARRHEA IN ONE TO THREE YEARS CHILDREN AT AMPLAS HEALTH CENTER IN 2015 - Ashry Ramadhana Ginting; Amelia Eka Damayanty (Universitas Muhammadiyah Sumatera Utara, 2020)
Nutritional status is a body condition as a result of food consumption and infection status. Nutritional status can be a risk factor of diarrhea. The aim is to determine the correlation of nutritional status with the occurrence of acute diarrhea in children beetween one to three years old at Puskesmas Amplas in 2015. This research is an analytic method of cross sectional and analysis of Chi Square. Using a secondary data from medical records of Puskesmas Amplas. All of bad-nourished respondence often suffering an acute diarrhea within one month. A well-nourished respondence who often suffer from acute diarrhea is 16,7%, and all of obese respondence often suffering an acute diarrhea. There is a correlation between the nutritional status with the occurrence of acute diarrhea with p value is 0,000 (p<0,05) in this research